The ritual world of Paul the Apostle: metaphysics, community and symbol in 1 Corinthians 10-11 - Lakey, Michael J. (Library of New Testament studies, 2019)
Michael Lakey explores the theological significance of the rituals of Baptism and the Lord's Supper in Pauline theology, with the argument culminating in an analysis of the significance of ritual dining in 1 Corinthians 10:14-22 and the Lord's Supper in 1 Corinthians 11:17-34. By contrast with 'social world' forms of comparison between rituals in the Pauline communities and other communities in antiquity, this study focuses primarily upon the theologically integrating function these rituals perform in relation to Paul's theology and ethics. Lakey builds upon Clifford Geertz's systemic understanding of religion by showing how, for Paul, Baptism and the Lord's Supper facilitate specific connections between his metaphysics on the one hand, and the form or pattern of life he enjoins upon his churches on the other. This volume considers precisely what - given his theological and ethical premises - Paul's underlying beliefs regarding these ritual events may have been, allowing for a preliminary discussion of specific lines of post-interpretation in the early patristic period. --